Brain microangiopathy and macroangiopathy share common risk factors and biomarkers. (March 2016) - Bang, Oh Young; Chung, Jong-Won; Ryoo, Sookyung; Moon, Gyeong Joon; Kim, Gyeong-Moon; Chung, Chin-Sang; Lee, Kwang Ho
Abstract: Aims: Besides carotid or cardiac embolism, stroke can occur via microangiopathy (small arterial disease [SAD]) and macroangiopathy (intracranial atherosclerotic stroke [ICAS]) of the intracranial vasculature. There have been efforts to identify risk factors specific to microangiopathy and macroangiopathy, including vascular risk factors, and protein and genetic biomarkers. We hypothesized that despite the anatomic and pathophysiological differences between microvessels and macrovessels, microangiopathy and macroangiopathy share common risk factors during disease progression. Methods: Among 714 patients with acute infarctions within middle cerebral artery territory, 126 with SAD and 116 with ICAS were included in this study. Subclinical microangiopathy (degree of leukoaraiosis) and macroangiopathy (number of tandem stenosis) was graded in each patient. Inflammatory biomarkers (C-reactive protein, E-selectin, and LpPLA2), endothelial dysfunction (asymmetric dimethylarginine, urinary albumin-to-creatinine ratio, endostatin, and homocysteine), atherogenesis (lipoprotein(a), adiponectin, and resistin), and renal function (creatinine clearance and estimated glomerular filtration rate) were assessed. Results: Compared with the patients with isolated SAD, those with isolated ICAS were younger, were current smokers, and showed higher apoB levels (p < 0.05 in all cases). However, with the progression of subclinical microangiopathy, asymptomatic macroangiopathy worsened and vice versa . No significant differences in risk factors were observed between advanced SAD and ICAS. Decreased renal function was independently associated with progression of microangiopathy and macroangiopathy. Markers of endothelial dysfunction, but not the other markers, were significantly related to creatinine clearance level. Conclusions: Mild to moderate loss of renal function is strongly associated with both intracranial microangiopathy and macroangiopathy. Endothelial dysfunction may be associated with this relationship. Highlights: Cerebral micro- and macroangiopathy often coexist. With the progression of subclinical microangiopathy, asymptomatic macroangiopathy worsens and vice versa . Risk factors differed between microangiopathy and macroangiopathy at early-stages but not at advanced stages. Loss of renal function was independently associated with progression of both microangiopathy and macroangiopathy.